2023
DOI: 10.1111/apa.16690
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of parental values during prenatal decisions about treatment options after extremely premature birth

Abstract: Parents need to be involved in prenatal decisions about neonatal treatment if their baby is likely to be born extremely premature -in the so-called grey zone, which is between 22 and 26 weeks of gestation, depending on time, country and culture. [1][2][3] The two treatment options in this grey zone are intensive care and comfort care.Intensive care treatment comes with great uncertainty regarding the outcome: some infants will not survive, some will go through life with one or more disabilities, and others wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
(186 reference statements)
0
9
0
Order By: Relevance
“…Presentation of positive cases by the physician may also be supportive. However, studies have also shown that parents should not be given false hope 14,15,18 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Presentation of positive cases by the physician may also be supportive. However, studies have also shown that parents should not be given false hope 14,15,18 …”
Section: Discussionmentioning
confidence: 99%
“…However, studies have also shown that parents should not be given false hope. 14,15,18 The main argument in favour of palliative care was not wanting to allow their infant to live a painful life without participation in society and with a reduced quality of life. This reasoning was also related to the decision for or against prenatal diagnostic measures at the beginning of pregnancy.…”
Section: Nevertheless the Question Remains Open Whether And To Whatmentioning
confidence: 99%
“…The PPKQ includes an overall score and 8 subscale scores representing knowledge in the SMFM-, AAP-, and ACOG-recommended domains: (1) long-term outcomes, (2) variability in due date estimation, (3) general prematurity knowledge, (4) lowest GA needed for survival, (5) factors influencing preterm birth outcome, (6) treatment options, (7) short-term outcomes, and (8) advocacy. The long-term outcomes subscale of the PPKQ was selected as the primary outcome because parent knowledge of long-term outcomes is often worse than short-term outcomes despite the centrality of long-term outcomes in periviable decision-making . The PPKQ can be scored as a sum or percentage correct.…”
Section: Methodsmentioning
confidence: 99%
“…The long-term outcomes subscale of the PPKQ was selected as the primary outcome because parent knowledge of long-term outcomes is often worse than short-term outcomes 19 despite the centrality of long-term outcomes in periviable decision-making. 29 The PPKQ can be scored as a sum or percentage correct. The 25-week instrument is available (eMethods in Supplement 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…A review by de Boer et al 4 looks at parents' perspectives about making prenatal decisions regarding treatment for babies born at the limit of viability. It is accompanied by a perspective, where the parents of an infant born at 24 weeks of gestation share their experiences 5 after an unexpected pregnancy was discovered at 18 weeks.…”
Section: Parents Share Their Views On Making Decisions At the Limits ...mentioning
confidence: 99%